Mitochondrial dynamics and reactive oxygen species initiate thrombopoiesis from mature megakaryocytes - Poirault-Chassac, Sonia (Blood Adv, 2021)
Blood platelets are essential for controlling hemostasis. They are released by megakaryocytes (MKs) located in the bone marrow, upon extension of cytoplasmic protrusions into the lumen of bone marrow sinusoids. Their number increases in postpulmonary capillaries, suggesting a role for oxygen gradient in thrombopoiesis (ie, platelet biogenesis). In this study, we show that initiation of thrombopoiesis from human mature MKs was enhanced under hyperoxia or during pro-oxidant treatments, whereas antioxidants dampened it. Quenching mitochondrial reactive oxygen species (mtROS) with MitoTEMPO decreased thrombopoiesis, whereas genetically enhancing mtROS by deacetylation-null sirtuin-3 expression increased it. Blocking cytosolic ROS production by NOX inhibitors had no impact. Classification according to the cell roundness index delineated 3 stages of thrombopoiesis in mature MKs. Early-stage round MKs exhibited the highest index, which correlated with low mtROS levels, a mitochondrial tubular network, and the mitochondrial recruitment of the fission activator Drp1. Intermediate MKs at the onset of thrombopoiesis showed high mtROS levels and small, well-delineated mitochondria. Terminal MKs showed the lowest roundness index and long proplatelet extensions. Inhibiting Drp1-dependent mitochondrial fission of mature MKs by Mdivi-1 favored a tubular mitochondrial network and lowered both mtROS levels and intermediate MKs proportion, whereas enhancing Drp1 activity genetically had opposite effects. Reciprocally, quenching mtROS limited mitochondrial fission in round MKs. These data demonstrate a functional coupling between ROS and mitochondrial fission in MKs, which is crucial for the onset of thrombopoiesis. They provide new molecular cues that control initiation of platelet biogenesis and may help elucidate some unexplained thrombocytopenia.